ROMANIAN EDUCATION SYSTEM SYNCOPEʼS REVEALED BY PISA TESTS. CAUSES OF SCHOOL FAILURE AND POSSIBLE AMELIORATIVE INTERVENTIONS - ION ALBULESCU; MIRELA ALBULESCU (Studia Universitatis Babes-Bolyai, 2012)
ABSTRACT. PISA type tests involving Romanian students in 2000 and until now have led to poor results, highlighting that the education system in Romania has many weaknesses. The national test results are not satisfactory. Of course, there are many students who achieve a higher level of academic preparation, proven in many situations. Schools proclaim its success citing their achievements. Nevertheless, the situation of school failure for many of their colleagues need urgent improvement interventions in terms of material and financial resources, school curriculum, learning strategies, improving teacher. In this study, we present in a synthetic manner, the undesirable situation, the causes that we believe generated it and possible solutions.